2021
DOI: 10.1007/s13555-021-00652-3
|View full text |Cite
|
Sign up to set email alerts
|

Methoxy-Monobenzoylmethane Protects Skin from UV-Induced Damages in a Randomized, Placebo Controlled, Double-Blinded Human In Vivo Study and Prevents Signs of Inflammation While Improving the Skin Barrier

Abstract: Introduction: Sun protection is important in skin care and requires special attention as inefficient protection might trigger skin pathologies including polymorphic light eruption (PLE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Skin photoaging is a complicated process in which skin changes are caused by persistent ultraviolet (UV) exposure [1][2][3]. Epidemiological studies and surveys have shown that skin photoaging contributes to the development of numerous skin disorders and skin tumors [4,5]. Public health concerns regarding sun exposure on the skin have grown substantially in recent years as people recognize photoaging damages their health and beauty.…”
Section: Introductionmentioning
confidence: 99%
“…Skin photoaging is a complicated process in which skin changes are caused by persistent ultraviolet (UV) exposure [1][2][3]. Epidemiological studies and surveys have shown that skin photoaging contributes to the development of numerous skin disorders and skin tumors [4,5]. Public health concerns regarding sun exposure on the skin have grown substantially in recent years as people recognize photoaging damages their health and beauty.…”
Section: Introductionmentioning
confidence: 99%